An evaluation of the Christ’s ascension gifts among selected Penteco/Charismatic leaders in Kumasi. - Opoku, Samuel Nhyira (KNUST, 2025)
A Thesis Submitted In Partial Fulfilment of the Requirement for the Award of the Master of Philosophy (MPhil.) Degree in Religious Studies.